Comprehensive analysis of Hibisci mutabilis Folium extract’s mechanisms in alleviating UV-induced skin photoaging through enhanced network pharmacology and experimental validation - Chen, Wenyuan; Deng, Qin; Deng, Bili; Li, Yueping; Fan, Gengqi; Yang, Fangfang; Han, Wei; Xu, Jian; Chen, Xiaolan (Frontiers in Pharmacology, 2024)
Background: Skin photoaging induced by ultraviolet A (UVA) and ultraviolet B (UVB) radiation manifests as skin roughness, desquamation, pigmentation, and wrinkle formation. Current treatments, such as sunscreen, hormones, and antioxidants, have limitations and side effects. Traditional Chinese Medicine Hibisci Mutabilis Folium (HMF), or Mu-Fu-Rong-Ye in Chinese name, refers to the dried leaves of the plant Hibiscus mutabilis L., which belongs to the Malvaceae family. It has been used traditionally to treat acute mastitis, parotitis, neurodermatitis, burns. The reported activities of HMF include anti-inflammatory and anti-oxidant effects. However, the therapeutic potential of HMF in preventing and treating UV-induced skin photoaging remains unexplored.Objective: This study aimed to investigate the protective effects of HMF extract (EHMF) against UV-induced skin photoaging and the underlying mechanisms of action, by using network pharmacology and experimental verification. Methods: Network pharmacology was employed to identify the effective chemical components of EHMF. Potential targets were identified via PPI network analysis. Representative compounds were characterized using UPLC-MS/MS. In vitro validation involved assessing HaCaT cell viability, observing live/dead cell staining through fluorescence microscopy, and measuring inflammatory factors using ELISA. For in vivo validation, a UV-induced skin photoaging mice model was treated transdermally with EHMF or Methotrexate daily for 7 days. Dermatitis severity, skin morphology, and collagen fiber pathology were evaluated. Inflammatory cytokine and protein expression in dorsal skin lesions was confirmed using Elisa Kits, Western blot and immunohistochemistry. Results: A total of 22 active ingredients of EHMF were identified. GO enrichment and KEGG pathway analyses revealed a focus on inflammatory signaling pathways.In vitro experiments showed that EHMF significantly reduced UV-induced inflammatory factors in HaCaT cells and improved cell survival rates. In vivo, EHMF alleviated back skin lesions in UV-exposed mice, reducing epidermal and dermal thickening and pathological inflammatory cell infiltration. It also decreased abnormal MMP-9 expression and collagen fiber proliferation, along with levels of inflammatory factors like TNF-α, IL-6, IL-17, and EGFR. Western blot and immunohistochemistry results indicated that the over-activation of the AKT-STAT3 signaling pathway was inhibited. Conclusion: EHMF effectively reduced UV-induced skin damage, inflammation, and wrinkles, providing strong support for its clinical application as a dermatological agent.